Study of the diffusion characteristics of hypericin using fluorescence correlation spectroscopy - Chiang, Serene Xiu Ting. (2011)
This project aims to study on the fluorophore (hypericin) uptake (diffusion rate) through experimental studies by implementation of fluorescence correlation spectroscopy. Instead of using biological cells, fluorophore with the similar excitation and emission spectra as the fluorophores which is going to be administered into the biological cell is needed. Currently, hypericin will be used. Analysis of the data collected at the end of the experiment will be carried out to verify on the result of findings. A discussion of the advantages and limitation of Fluorescence Correlation Spectroscopy (FCS) will also be discussed.